The Development of Protist Culture Medium to Improve Senior High School Studentâs Observation Skills - Sutrisnowati, Intan Indah; Mubarok, Ibnul; Priyono, Bambang (Journal of Biology Education, 2017)
Teachers and students have difficulty in observing protist spesies. The basic competence 3.5 oblige thestudents to apply the principle of protist grouping classification carefully and systematically. Therefore, thereshould be a media of culture protist along with its way and the studentsâ observation worksheet for protists.This research is aimed to develop the valid and effective culture media of protist for class practice activities inProtist Material. This research used Research and Development (R&D) method. Small scale trials weredone to 10 students using purposive random sampling. Big scale trials were done to 64 students. The validityof protist culture was scored using validity sheets by validator, then was analyzed in percentage description.The effectivity score of protist culture media was obtained based studentsâ processing skills score. The result ofthe research showed that protist culture media was considered valid by experts with the average score of90,1%. The observation of studentsâ skills showed that both classes of the research has classical grade of85,3% and 87,1%. Based on the results, it can be concluded that protist culture media with its guidance andstudentsâ observation worksheet was valid and effective to be used by Senior High School students.